Aplikasi Inventory Berbasis Web Pada PT Telkomsel NS Tasikmalaya - Gilang Permadi Khasani; Daniel Jahja Surjawan (Jurnal Teknik Informatika dan Sistem Informasi, 2016)
PT Telkomsel Regional Jawa Barat Network Service Tasikmalaya has a lot of inventory items with different serial number. These goods will be used by vendors in providing services to the public. Problems occurs when entering a serial number on each item because data collection is still manual. There is a problem upon return of goods to the center, that is known as the Return Merchandise Authorization or RMA abbreviated, when the Serial Number of the items in the RMA is often forgotten deactivated by the user, causing multiple input Serial Number. The purpose of this research is the ease of input Serial Number automatically generate by barcode includes reminder Serial Number features. In addition will be made also preparing reports on each of goods in accordance with the desired period.